Persekutuan Perdata Notaris Ditinjau dari Prinsip Kemandirian dan Prinsip Kerahasiaan pada Jabatan Notaris - Nadia Noor, Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The establishment of a civil partnership among notaries, governed by Article 20 of Law No. 2 of 2014 amending Law No. 30 of 2004 on Notary Position, introduces new dynamics to notarial principles, particularly the principles of independence and confidentiality outlined in Article 16 of the same law. This development raises concerns about potential disharmony, as forming a Notary Association could compromise notarial independence. When multiple notaries operate within one association, they may find it challenging to maintain the requisite impartiality and confidentiality specified by law. Upon analyzing these issues, several conclusions emerge. Firstly, the regulations governing notary civil partnerships appear sufficient and compatible with the core principles of notarial practice. Notaries are obligated to conduct themselves professionally, adhering strictly to legal statutes and the ethical code of notaries, which stress independence and confidentiality. Hence, while engaging in civil partnerships as permitted by Article 20, notaries must uphold these moral and legal standards, ensuring their activities remain in alignment with the law and ethical guidelines. Secondly, the formation of notary civil partnerships has implications for maintaining the principles of independence and confidentiality. The essence of a notary's independence as a public officer is critical, encompassing structural, functional, and financial independence. Any association among notaries could potentially undermine these fundamental principles, as notaries may face challenges in preserving their autonomy and impartiality when operating within a partnership structure. The legal framework stipulating notarial responsibilities emphasizes the necessity for notaries to operate independently, free from external influences. In summary, while Article 20 allows for notarial civil partnerships aimed at enhancing service delivery to the public, it necessitates careful adherence to the principles of independence and confidentiality integral to notarial duties. The challenge lies in balancing the benefits of collaboration with the imperative of maintaining the integrity and autonomy of the notarial function as prescribed by law.